Students' perspectives of assessment at the tertiary level of education. - Diaz, Ilonka Constanza Babarovich (My University, 2009)
University students worldwide regularly encounter assessments in their courses and the results obtained are used to make important decisions about their movement from one year of study to the next. This makes students vital stakeholders in the assessment practices of institutions and illustrates how issues related to the topic of assessment and assessment practices are critical to students. Many authors and researchers advocate the idea that the perspectives of students’ themselves are important wherever questions of assessment arise. Furthermore, assessments take on various forms and are understood and therefore utilised in a particular manner depending on their context. This study thus aimed to describe assessments used at a specific South African university from the students’ perspective. Seventeen third year level Psychology students participated by completing a demographic questionnaire and taking part in one of four focus groups which were transcribed. The data were analysed using thematic content analysis. The research yielded results pertaining to many different aspects of assessment. Participants perceived the purposes of assessment in the same manner as described in the literature, namely to measure knowledge, ability to cope and institutional standards. They viewed each form of assessment (multiple choice tests, open-ended test and examinations, essay assignments and group work) as having a specific purpose and different advantages and disadvantages and indicated that they prepared for each type of assessment using different strategies, depending on the form. Participants understood assessments in terms of the types of task that each required them to complete but were more concerned about the conditions under which they were expected to complete them. The time constraint element in particular was viewed as detracting from performance rather than as part of the assessment task. Other individual and contextual factors were perceived as important but were often not accounted for or able to be accounted for in assessments. Participants appeared motivated to succeed by achieving high marks rather than by achieving the intended course outcomes and assessment purposes and time management was identified as an important aspect of coping. In general, the participants seemed to perceive assessment and the various forms thereof in a similar manner and in line with literature.
Keywords: Student assessment; Tertiary education